Advanced Control of Piezoelectric Micro-/Nano-Positioning Systems - Xu, Qingsong; Tan, Kok Kiong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book explores emerging methods and algorithms that enable precise control of micro-/nano-positioning systems. The text describes three control strategies: hysteresis-model-based feedforward control and hysteresis-model-free feedback control based on and free from state observation. Each paradigm receives dedicated attention within a particular part of the text. Readers are shown how to design, validate and apply a variety of new control approaches in micromanipulation: hysteresis modelling, discrete-time sliding-mode control and model-reference adaptive control. Experimental results are provided throughout and build up to a detailed treatment of practical applications in the fourth part of the book. The applications focus on control of piezoelectric grippers. Advanced Control of Piezoelectric Micro-/Nano-Positioning Systems will assist academic researchers and practising control and mechatronics engineers interested in suppressing sources of nonlinearity such as hysteresis and drift when combining position and force control of precision systems with piezoelectric actuation. Advances in Industrial Control aims to report and encourage the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control.
Introduction -- Part I Hysteresis Model-Based Feedforward Control -- Feedforward Control Based on an Inverse Hysteresis Model -- Feedforward Control without Modeling Inverse Hysteresis -- Part II Hysteresis-Model-Free, State-Observer-Based Feedback Control -- Model Predictive Discrete-Time Sliding-Mode Control -- Model Predictive Output Integral Discrete-Time Sliding-Mode Control -- Part III Hysteresis-Model-Free, State-Observer-Free Feedback Control -- Digital Sliding-Mode Control of Second-Order Systems -- Digital Sliding-Mode Control of High-Order System -- Digital Sliding-Mode Prediction Control -- Model-Reference Adaptive Control with Perturbation Estimation -- Part IV Applications to Micromanipulation -- Adaptive Impedance Control of Piezoelectric Microgripper -- Position/Force-Switching Control of a Miniature Gripper. Glossary.
Keywords: Control engineering; Microtechnology; Microelectromechanical systems; Industrial engineering; Production engineering; Mechatronics; Control and Systems Theory; Microsystems and MEMS; Industrial and Production Engineering; Mechatronics